2008
DOI: 10.1158/0008-5472.can-07-5171
|View full text |Cite
|
Sign up to set email alerts
|

Superior Activity of Fusion Protein scFvRit:sFasL over Cotreatment with Rituximab and Fas Agonists

Abstract: The clinical efficacy of the CD20-specific chimeric monoclonal antibody rituximab is significantly hampered by intrinsic or acquired resistance to therapy. Rituximab activates antibodydependent cellular cytotoxicity/complement-dependent cytotoxicity-dependent lysis but also induces apoptosis by cross-linking of its target antigen CD20. Recent reports indicate that this apoptotic activity of rituximab can be synergized by cotreatment with Fas agonists. Here, we report on a strategy designed to exploit and optim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
36
0

Year Published

2008
2008
2013
2013

Publication Types

Select...
5
2
2

Relationship

3
6

Authors

Journals

citations
Cited by 43 publications
(37 citation statements)
references
References 26 publications
1
36
0
Order By: Relevance
“…Nonetheless, the inhibition of rituximab binding by Rp5-L (and Rp15-C) was also observed with other human B lymphoid cells (Ramos and LG-2) and with primary CD20 ϩ lymphocytes (data not shown). Moreover, an inhibitory effect in the human Burkitt's lymphoma cell line BJAB was recently reported for the Rp5-Lfamily peptide Rp10-L (bearing the Rp5-L motif ͳWPxWLEʹ (13, 16)), which competed with the binding of a rituximab-derived construct (36).…”
Section: Discussionmentioning
confidence: 98%
“…Nonetheless, the inhibition of rituximab binding by Rp5-L (and Rp15-C) was also observed with other human B lymphoid cells (Ramos and LG-2) and with primary CD20 ϩ lymphocytes (data not shown). Moreover, an inhibitory effect in the human Burkitt's lymphoma cell line BJAB was recently reported for the Rp5-Lfamily peptide Rp10-L (bearing the Rp5-L motif ͳWPxWLEʹ (13, 16)), which competed with the binding of a rituximab-derived construct (36).…”
Section: Discussionmentioning
confidence: 98%
“…A genetically engineered fusion protein, scFvRit:sFasL, containing a rituximab-derived antibody fragment and Fas ligand was successfully used in malignant B cells [129] (Fig. 4).…”
Section: Enhancing Apoptosis In Rituximab Therapymentioning
confidence: 99%
“…In accordance with this hypothesis, we and others showed that fusion proteins composed of an N-terminal cell surface antigen-recognizing single chain fragment (scFv) and soluble FasL exert on antigen positive cells a several order of magnitude higher activity than on antigen negative cells. [265][266][267] Thus, cell surface retention of scFv-FasL fusion proteins by interaction with their cognate cell surface antigens constitutes pseudo-membrane FasL (see Fig. 5).…”
Section: Cell Surface Antigen-restricted Activation Of Fasmentioning
confidence: 99%